2019
DOI: 10.1038/s41598-018-37898-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights reveal Anti-microbial Gene Regulation of Piglet Intestine Immune in response to Clostridium perfringens Infection

Abstract: LncRNA play important roles in regulation of host immune and inflammation responses in defending bacterial infection. Clostridium perfringens (C. perfringens) type C is one of primary bacteria leading to piglet diarrhea and other intestinal inflammatory diseases. For the differences of host immune capacity, individuals usually show resistance and susceptibility to bacterial infection. However, whether and how lncRNAs involved in modulating host immune resistance have not been reported. We have investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Indeed, PAMPs are recognized by several families of innate receptors, including the NOD-like receptors ( Tourlomousis et al., 2020 ), the Toll-like receptors ( Mathur et al., 2012 ), the C-type lectin receptors ( Roesner et al., 2019 ), the RIG-like helicases ( Asaka et al., 2009 ), and cytosolic DNA sensors ( Sisquella et al., 2017 ), which in turn help to detect invading pathogenic microbes and prevent disease progression. Growing evidence indicates that C. perfringens interact with the host to drive the innate response, and Toll-like receptors and NOD-like receptors were implicated in C. perfringens recognition ( Huang et al., 2019 ; Yamamura et al., 2019 ). Hence, investigating the innate immune mechanisms of host resistance to C. perfringens will be conducive to implementing pathogen control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PAMPs are recognized by several families of innate receptors, including the NOD-like receptors ( Tourlomousis et al., 2020 ), the Toll-like receptors ( Mathur et al., 2012 ), the C-type lectin receptors ( Roesner et al., 2019 ), the RIG-like helicases ( Asaka et al., 2009 ), and cytosolic DNA sensors ( Sisquella et al., 2017 ), which in turn help to detect invading pathogenic microbes and prevent disease progression. Growing evidence indicates that C. perfringens interact with the host to drive the innate response, and Toll-like receptors and NOD-like receptors were implicated in C. perfringens recognition ( Huang et al., 2019 ; Yamamura et al., 2019 ). Hence, investigating the innate immune mechanisms of host resistance to C. perfringens will be conducive to implementing pathogen control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…All of the raw sequencing data were deposited into a sequence read archive (SRA), under accession number PRJNA399620, at the National Center for Biotechnology Information (NCBI). Based on previous gene expression profiles obtained from RNA-seq [ 21 ], a total of 25491 mRNAs were identified in the ileum tissues of piglets. Among these, we screened genes with fold change of ≥1.5, p value < 0.05, and FPKM value > 1 from IR vs. IC and IS vs. IC as differentially expressed genes.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are no published literature reports on differential expression and regulation of genes related to the MAPK signaling pathway in diarrhea piglets caused by C. perfringens type C. In our preliminary transcriptome study, we have identified 25491 mRNAs and 3740 lncRNAs in the ileum tissues of piglets infected with C. perfringens type C [ 21 ]. Building on this, the present work was designed to further investigate the expression patterns of MAPK signaling pathway genes in the ileum tissues of infected piglets using quantitative real-time polymerase chain reaction (qRT-PCR).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine endemic diarrhea virus (PEDV) infection modulates lncRNA expression patterns in the ileum of IPEC-J2 cell lines and piglets and activates the ileal immune system ( Chen et al, 2019 ). In piglet diarrhea caused by C. perfringens type C, many lncRNAs and mRNAs modulate drug resistance and susceptibility in piglets through immune-related pathways ( Huang et al, 2019 ). Although many lncRNAs have been reported to be associated pig diarrhea, few lncRNAs have been identified that are closely associated with CPB2 toxin-induced diarrhea in piglets.…”
Section: Introductionmentioning
confidence: 99%